Critical Construction Readiness Factors for Bridge Projects - Mohamed, Hany Abd Elshakour; Hasaballah, Anas G.; El-Kelesh, Adel M. (Civil Engineering Journal, 2024)
Egyptian investment in infrastructure projects is considerable, especially in bridge construction projects that commonly face delays, cost overruns, rework, and poor productivity. A proper construction readiness (CR) assessment can enhance project performance. This study aims to identify the critical factors that impact the CR of bridge projects in Egypt. Through a literature review and a pilot study with ten highly experienced professionals, a list of 43 construction readiness factors (CRFs) was prepared. To quantitatively rank these CRFs and identify the critical ones, a questionnaire was administered through structured interviews with 92 project managers and engineers experienced in bridge construction projects in Egypt. The participants represented the perspectives of contractors, owners, and consultants. A CRF with a normalized mean score greater than or equal to 0.5 was classified as a critical construction readiness factor (CCRF). For these CCRFs, agreement analysis among contractors, owners, and consultants was conducted using the Kruskal-Wallis test. The correlation strength was also investigated using Spearman's correlation. In total, 16 CCRFs were identified, with the top five: verification of underground utility locations, completion of land surveying work, issuance of clear and sufficient construction drawings, adequate geotechnical investigations, and obtaining all necessary permits and approvals from local authorities. This study provides practitioners with critical factors necessary for assessing the CR of bridge projects in Egypt. From an academic standpoint, it enhances understanding of CR, which is rarely discussed. Doi: 10.28991/CEJ-SP2024-010-015 Full Text: PDF